Prehospital Factors Associated with Refractory Traumatic Arrest - Jeong Hun Lee; Yong Won Kim; Tae Youn Kim; Sanghun Lee; Han Ho Do; Jun Seok Seo; Seung Chul Lee (Emergency Medicine International)
Objective. Identification of the prehospital factors associated with a poor prognosis of immediate traumatic arrest should help reduce unwarranted treatment. We aim to reveal the clinical factors related to death after traumatic arrest on the scene. Methods. We performed a multicenter (4 tertiary hospitals in urban areas of South Korea) retrospective study on consecutive adult patients with trauma arrest on scene who were transferred by fire ambulance from January 2016 to December 2018. Patients with death on arrival in the emergency room (ER) were excluded. Prehospital data were collected from first aid records, and information on each patient’s survival outcome in the ER was collected from an electronic database. Patients were divided into ER death and ER survival groups, and variables associated with prehospital trauma were compared. Results. A total of 145 (84.3%) and 27 (15.7%) patients were enrolled in the ER death and survival groups, respectively. Logistic regression analysis revealed that asystole (OR 4.033, 95% CI 1.342–12.115, p = 0.013) was related to ER death and that ROSC in the prehospital phase (OR 0.100, 95% CI 0.012–0.839, p = 0.034) was inversely related to ER death. In subgroup analysis of those who suffered fall injuries, greater height of fall was associated with ER death (15.0 (5.5–25.0) vs. 4.0 (2.0–7.5) meters, p = 0.001); the optimal height cutoff for prediction of ER death was 10 meters, with 66.1% sensitivity and 100% specificity. Conclusions. In cases of traumatic arrest, asystole, no prehospital ROSC, and falls from a greater height were associated with trauma death in the ER. Termination of resuscitation in traumatic arrest cases should be done on the basis of comprehensive clinical factors.